Plant Response To Organic Fertilizer In Panca Agung Village, Bulungan District - Hariyati, Tati; Putra, Marlan Unmani; S, Sabarudin; Suryanta, Ipung; Fikri, M.; Lesmana, Rina (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Agriculture in Indonesia generally still depends on the use of chemical fertilizers, where chemical fertilizers can increase plant productivity, but the presence of chemical fertilizers if used continuously in the long term will have an impact on damage to the soil, environment and ecosystem, resulting in the soil becoming hard due to the accumulation of waste. chemicals (residues). Panca Agung Village has the potential for quite fertile agricultural land, with many types of plants being cultivated such as vegetables, fruit, rice, banana trees and coconut trees. With this potential, existing waste can be used as raw material which can be processed into environmentally friendly organic fertilizer, which can be used as plant fertilizer to replace chemical fertilizers. The aim is to determine the response of plants to the application of organic fertilizer. The method used is in three stages, namely 1) Collection of waste raw materials, 2) making organic fertilizer, 3) Application of fertilizer to plants. The results obtained by applying organic fertilizer make the plants grow more fertile, the leaves appear to grow faster and the harvest time of the plants is faster. Based on the results, it can be concluded that applying organic fertilizer is no less than using chemical fertilizer, in terms of plant growth.